Educational credit as an independent type of crediting in the sphere of higher professional education (Путеводитель предпринимателя)
The article considers the educational credit as a standalone product of crediting in the sphere of higher professional education. The analysis of terminological approaches to defining the essence of banking, consumer and public types of credit and are their characteristic features. The author considered the pilot project «Education» implemented by the agency for housing mortgage lending. Substantiated conclusion about the existence of a generalized approach to the content of the considered species of the credit and the need to address the educational loan as an independent type of lending available to the applicants, which enjoys the demand of the population and commercially sold. The author of the article considers the pilot project «Education», which is realized by the agency of mortgage housing crediting. The conclusion about the need for educational loan lending as a separate product that is available for applicants who are in demand of the population and tradable.